CURRENT AND PROJECTED CHANGES IN HYDROLOGICAL CYCLE COMPONENTS ACROSS BELARUS: PRECIPITATION, EVAPORATION AND RIVER RUNOFF (Proceedings of the YSU C: Geological and Geographical Sciences, 2026)
The study presents results of analyzing changes in the hydrological cycle across the territory of Belarus for 1945–2025 and projections for the period 2025–2050 under the SSP2 RCP4.5 scenario. Annual precipitation shows no significant trend, but summer precipitation decreases by 2–3 mm per decade, accompanied by a 30% increase in the frequency of heavy rainfall. Total evaporation has been increasing since 2004, which is not synchronized with the onset of climate warming. Water resources generated within the country have decreased by 17% over the last 10–15 years. In river regimes, winter runoff continues to increase while spring floods decrease; the frequency of hydrological droughts during the warm season has doubled. A 20% reduction in summer precipitation, a variation in total evaporation within 10%, and an average annual runoff close to the long term norm are projected, but with wide confidence intervals of 30–70%, which maintains the risk of extreme events, especially in the 2030s.
Keywords: climate change; extremes; rainfall; drought; streamflow; flood